The assistance of Er,Cr:YSGG laser in pulp injury related to anterior teeth trauma - Gülşah Balan; Harry Huiz Peteers; Serap Akyüz (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Erbium chromium or erbium lasers constitute preferred instruments for the preparation of that section of tooth adjacent to the pulp chamber rather than high-speed drills, especially in cases of dental injury. Their advantages can support modified operations in achieving optimum recovery and avoiding complications related to the healing process. Purpose: The aim of the study was to describe another modality of the assistance of erbium, chromium:yattrium-scandium-gallium-garnet (Er,Cr:YSGG) laser in traumarelated pulp injury affecting the anterior teeth. Case(s): The results of laser treatment applied to four pulp injuries of three children were analyzed in this case report. Case Management: Er,Cr:YSGG laser-assisted cavity preparation was performed without resort to a local anesthetic, the cavities being sealed with mineral trioxide aggregate (MTA). None of the cases demonstrated symptomatic or peri-radicular pathology during clinical or radiographic examinations. Conclusion: The results contained in this case report support the application in pediatric dentistry of a Er,Cr:YSGG laser to pulpotomy cavities as part of the treatment of traumatic pulpal injuries to permanent incisors.